Design of the Five Fastest Strategies to Create the Principle of Fairness for Students in Mathematics Learning - I Made Dharma Atmaja; Gusti Putu Suharta; Sariyasa Sariyasa; Gede Suweken (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
A review of aspects in the cognitive, affective, and psychomotor domains of students will be able to support the assessment process in learning, which is supported by the objectivity and fairness of teachers in providing assessments. Objective can be interpreted as an assessment based on facts without the influence of other factors such as likes or dislikes. While fair can be interpreted as equal treatment in accordance with the proportions that should be and appropriately. In learning mathematics there are stages that provide opportunities for students to present their work in front of the class. There are two possible conditions faced by the teacher when providing the stages of this session, namely that none of the students took the initiative to come forward, there were few students who were interested, and there were many students who were interested. The implementation of the five-fastest strategy can be used as an alternative to create the principle of fairness for students, especially the opportunity to appear in front of the class to convey the results of their work or answers to math problems given by the teacher.